ECONOMIC FEASIBILITY OF COMPOSITE FISH CULTURE IN LEASED-IN VILLAGE TANKS OF KANYAKUMARI DISTRICT - SURESH, R. (Journal of Indian Fisheries Association, 2015)
Kanyakumari district belonging to the high rainfall zone has resource advantages for composite fish culture in the leased-in village tanks. There are more than 400 fish farmers operating in leased-in tanks following composite fish culture under the FFDA programme. To estimate the economic feasibility and financial viability of the enterprise, the present study was taken up. 38 fish farmers selected from the district provided the necessary information like capital investment, costs and return and constraints. The data collected were analysed and a farm nearest to the average farm situation was taken as the representative farm. Investment criteria like PayBacl Period (PBP), Simple Rate f Returns (SRR), Net Present Value (NPV) and Benefit Cost Ratio (BCR) were estimated taking into account a period of 10 years, the period for which the village tanks are leased-out to fish farmers under the FFDA programme. The analysis indicated the profitability of composite fish culture in village tanks in the district and the results are discussed with recommendations.